Effectiveness of Education and Supplementary Feeding Interventions in Stunting Prevention: A Systematic Review - Ernawati, Ernawati; Puspitawanti, Gita Indri; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (LPPM Institut Pendidikan Nusantara Global, 2026)
This coverage review aims to identify the effectiveness of educational interventions and supplementary feeding as preventive measures against stunting among children aged 6 to 59 months in various countries. The methodology applied in this study follows the PRISMA guidelines to ensure a systematic and transparent review process. A comprehensive literature search was conducted through relevant electronic databases, including Google Scholar, PubMed, and ScienceDirect, focusing on articles published between 2020 and 2024. Only studies written in English and examining supplementary feeding practices for children within the specified age range were included. From the total number of articles initially identified, 11 studies met all eligibility criteria and were analyzed in depth. The findings indicate that educational interventions for parents and the provision of diverse supplementary foods such as milk-based products, eggs, lipid-based supplements, and locally sourced nutrient-dense foods play a significant role in improving weight and height outcomes in young children. These foods, which are rich in protein, vitamins, minerals, and other essential micronutrients, contribute substantially to supporting growth and preventing nutritional deficiencies. Furthermore, the results highlight that appropriate feeding practices by caregivers, particularly mothers, are crucial for the successful prevention of stunting. Overall, this review concludes that proper supplementary feeding strategies, combined with strengthened parental education on nutrition, can effectively promote optimal growth and development in children under five. Continuous efforts to improve community awareness, enhance feeding practices, and ensure accessibility of nutritious supplementary foods are essential strategies to reduce stunting prevalence globally